DEFINING A MUTUAL RELATIONSHIP AMONG THE BODY POSTURE, PHYSICAL CONDITION (FITNESS) AND REGULAR PHYSICAL ACTIVITY IN CHILDREN OF YOUNG SCHOOL-AGE - VOJTÍKOVÁ, Lenka (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2020)
Introduction. The main focus of our study was to evaluate the body posture in a group of 147 children aged 6.4 – 9.8 y. In the study, we tried to find a statistically significant relationship among a body posture, particular components of physical fitness and the amount of physical activity. Methods. To evaluate the body posture, a modified Matthias test was used. To test the physical fitness, the UNIFITTEST 6-60 was used, including defining the somatotypes and it´s specific features. To find out the amount of physical activity, a questionnaire was used, which was completed by parents due to the age of the respondents. Results. The results have shown disbalances in body posture in the observed group of young school-age children. In total 53.1 % of children of the monitored group had poor body posture. Based on the t-test, statistically significant difference in the evaluation of the quality of body posture was found between the groups of boys and girls (t=3.21; p<0.01), boys scored worse in the body posture test. Only a feeble correlation between the quality of the body posture and the amount of organized physical activity was measured in the group of girls (rs=-0.24; p<0.05) – girls with a higher volume of extracurricular physical activities had better results in the evaluation of posture; however, this effect was small. The study has not shown any relations between the body posture and the individual components of physical fitness. The quality of the body posture is neither related to the amount of subcutaneous fat nor the BMI. Those children who practice some organized physical activity less frequently did worse in most tests concerning physical endurance. Their amount of subcutaneous fat was higher than in children who often participate in various after school activities more. The results of tests of fitness in both groups of girls and boys are even, the only statistically significant difference between these groups was found in the test result of the maximum reach while sitting, boys scored worse in this test (Z=-2,686; p<0.01). Conclusion. More than half of the children of young school-age in the observed group children had poor body posture or at leas some posture deviation, the boys had a worse posture than the girls. The results of our research did not show a relationship between posture and performance in physical fitness tests. There was no evidence of a relation between body posture and body composition (measured by amount of subcutaneous fat and BMI). Sufficient physical activity probably has a positive effect on increasing fitness, but the relationship to posture is inconclusive.